2018
DOI: 10.1186/s11671-018-2530-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bi Distribution in Epitaxial GaAsBi by Aberration-Corrected HAADF-STEM

Abstract: The Bi content in GaAs/GaAs1 − xBix/GaAs heterostructures grown by molecular beam epitaxy at a substrate temperature close to 340 °C is investigated by aberration-corrected high-angle annular dark-field techniques. The analysis at low magnification of high-angle annular dark-field scanning transmission electron microscopy images, corroborated by EDX analysis, revealed planar defect-free layers and a non-homogeneous Bi distribution at the interfaces and within the GaAsBi layer. At high magnification, the qHAADF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…PLEASE CITE THIS ARTICLE AS DOI: 10.1063/1.5140447 (b) a structural disorder due to annealing that can be attributed to the Bi-segregation followed by a structural relaxation in the QW region. This evidence is compelling if we compare with Bi clusters reported by Beladés et al [31]. Nevertheless, corroborating with HR-XRD, the GaAs buffer layer is not visible in the TEM images indicating, therefore, the existence of the same vertical lattice parameter than that from GaAs substrate.…”
Section: Methods and Experimental Detailssupporting
confidence: 88%
“…PLEASE CITE THIS ARTICLE AS DOI: 10.1063/1.5140447 (b) a structural disorder due to annealing that can be attributed to the Bi-segregation followed by a structural relaxation in the QW region. This evidence is compelling if we compare with Bi clusters reported by Beladés et al [31]. Nevertheless, corroborating with HR-XRD, the GaAs buffer layer is not visible in the TEM images indicating, therefore, the existence of the same vertical lattice parameter than that from GaAs substrate.…”
Section: Methods and Experimental Detailssupporting
confidence: 88%
“…The fact that Bi QDs orient randomly eliminated the possibility to analyze them using HRXRD reciprocal space mapping technique, leaving HRTEM as the only available technique to investigate the properties of Bi QDs in detail. There is still no clear agreement on Bi QD orientation in the literature, some groups report that Bi is oriented such that Bi (102) is parallel to GaAs (220), while others claim that Bi nanoparticles are not coherent with the matrix . Our study supports that Bi QDs are oriented randomly within their host matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The authors proposed a mechanism of Bi QDs formation that relies on a spinodal surface decomposition at the early growth stages. Inhomogeneous Bi distribution after the annealing and formation of ≈12 nm size rh‐Bi nanoparticles in GaAs/GaAsBi/GaAs, is also reported . This group, however, found that Bi QDs are crystallographically incoherent with their GaAsBi matrix.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rather small Sb concentration ( ) in the Al Ga As Sb systems grown at LT results in the formation of NPs with an antimony concentration [ 25 ]. In the case of the LT-grown GaAs Bi with ( ), the NPs are composed of almost pure bismuth [ 26 , 27 , 28 ]. Such NPs have a rhobohedral atomic structure and almost spherical shape, with diameters around 10–20 nm.…”
Section: Introductionmentioning
confidence: 99%